How Classroom Acoustics Affect the Vocal Load of Teachers. (November 2015) - Durup, Nick; Shield, Bridget; Dance, Stephen; Sullivan, Rory; Gomez-Agustina, Luis
Abstract: In the UK the document BB93 Acoustic Design of Schools provides design guidance for refurbished and new classrooms. Traditionally, school acoustic design in the UK is concerned with the needs of the listener, rather than the voice ergonomics of the speaker. However, a recent survey undertaken by London South Bank University (LSBU) indicated that over 65% of the surveyed teachers had experienced voice problems during their career. This supports other studies suggesting that teachers have a significantly higher incidence of voice problems than the general population. In an effort to better understand the influence of classroom acoustic design on teachers' speech LSBU is undertaking measurements of teachers' voices in different classroom types. An Ambulatory Phonation Monitor (APM) is used to measure voice parameters (including the average speech sound level, fundamental frequency and phonation time) directly from the skin vibrations in the neck, thus eliminating the effects of other noise sources in the environment. The rooms involved are acoustically benchmarked separately to enable relationships between the voice data and acoustic parameters, such as unoccupied ambient noise levels and reverberation times, to be investigated. This paper will present the results of the field measurements to date, and discuss some of the findings.